Predicting Cloned Disease Resistance Gene Homologs (CDRHs) in Radish, Underutilised Oilseeds, and Wild Brassicaceae Species - Aldrin Y. Cantila; William J. W. Thomas; Philipp E. Bayer; David Edwards; Jacqueline Batley (Plants, 2022)
Brassicaceae crops, including Brassica, Camelina and Raphanus species, are among the most economically important crops globally; however, their production is affected by several diseases. To predict cloned disease resistance (R) gene homologs (CDRHs), we used the protein sequences of 49 cloned R genes against fungal and bacterial diseases in Brassicaceae species. In this study, using 20 Brassicaceae genomes (17 wild and 3 domesticated species), 3172 resistance gene analogs (RGAs) (2062 nucleotide binding-site leucine-rich repeats (NLRs), 497 receptor-like protein kinases (RLKs) and 613 receptor-like proteins (RLPs)) were identified. CDRH clusters were also observed in Arabis alpina, Camelina sativa and Cardamine hirsuta with assigned chromosomes, consisting of 62 homogeneous (38 NLR, 17 RLK and 7 RLP clusters) and 10 heterogeneous RGA clusters. This study highlights the prevalence of CDRHs in the wild relatives of the Brassicaceae family, which may lay the foundation for rapid identification of functional genes and genomics-assisted breeding to develop improved disease-resistant Brassicaceae crop cultivars.